Implementasi Model STEMPROCSI Studi Kasus Pada Program Studi Pendidikan Teknik Informatika dan Komputer - Karmila Suryani; Khairudin Khairudin (Universitas Negeri Padang, 2020)
This study is an implementation of the STEMProcsi model that aims to 1) Knowing the students ' understanding of learning Science, Technology, Engineering, and Mathemetic, Projects and Simulation (STEMProcSi). 2) to measure student skills in using the STEMProcsi components that produce a project, and 3) Assessing students' attitudes towards the STEMProcSi learning model. This research used 15 students as sample of Computer and Informatics Engineering Education (PTIK) in the odd semester of the academic year 2019/2020. The research procedure was carried out in trhee steps; 1) provides problems that are solved by concept maps using the XMIND application, 2) Complete calculations using the Microsoft Excel application, and 3) Create interactive products with the Scatch application. The research instrument uses a questionnaire with 5 liker scale. Based on data analysis, the results of this study indicate that the application of the STEMProcSi model can generate interest and enthusiasm of students in understanding the material, practice critical thinking, creative, communicative and collaborative and can produce an interactive product. Therefore it can be concluded that the STEMProcsi model is good to be used in the learning process for exact subject courses in tertiary institutions.